Kaizer effect in accoustic emission event from mechanical testing - Mohd Nurazlan, Md Ghazali (2010)
This thesis presents the Kaizer Effect in acoustic emission event from mechanical testing. Acoustic emission is a transient elastic wave generated by the rapid release of energy from localized source or sources within a material according to the ASTM E1316 standard. The purpose of this project is to study acoustic emission (AE) properties from mechanical testing during reload of specimen until fracture. The laboratory experiments are carried up in this project. The acoustic emission (AE) signal acquired on mild steel and aluminium specimens from tensile test and torsion test under reload-unload loading profile. Kaizer effect of acoustic emission in mild steel and aluminium, were validated by the experiment. The experimental results will show the event between the specimens. Acoustic emission (AE) sensors are used to detect AE event in stress situation. Each loading cycle would cause new damage inside the material and the response of material to the new loading cycle is different from the previous cycle. The parameter in acoustic emission such as energy, hits and RMS were recorded and analyzed from this experiment. As a result, almost all of tensile test method was achieve the Kaizer effect theory although certain of cycles have an error cause of external disturbance. From the observations, the hits data, energy and RMS data for mild steel show the large value compare to aluminum specimen. For torsion test, all graphs of hits, energy and RMS look similar with each other. The AE event generated continuously although the loading is in released condition. This situation mentions that, the method of torsion test is not suitable to carry out the Kaizer effect study. For the future work, this project can be further by changing another method to replace the torsion test method. Other method such as fatigue test also can be used to study Kaizer effect in acoustic emission. The scope of this research also can be expanded and developed with add more materials to analyze.